Effect of Udvartan therapy in Sthoulya (Obesity)-A Review - Chandrakar, Vinita; Vedpathak, Surendra; Kumar, Vipin; Patel, Kunal (International Research Journal of Ayurveda & Yoga, 2022)
In modern days in appropriate food habit is the main cause of Sthoulya(Obesity). It occurs as a result of a sedentary lifestyle, unhealthy eating habits, a lack of physical activity, mental stress, and other factors. It has reached pandemic proportions in India in the twenty-first century, impacting 5% of the population. Obesity is becoming more common in both children and adults every day. Obesity is linked to a variety of medical conditions (like hypertension, atherosclerosis and diabetes). lakshana and Chikitsa for Sthoulya is also described in detail by the Acharyas. It combines Shodhana and Shamana therapy in general. The Udavartana Karma, which has Kaphahara and Medohara properties Udvartana is a Panchakarma’s allied therapy that differs from Abhyanga in terms of application direction and pressure applied during the procedure. It’s a simple, low-cost operation with no side effects. [Udvartana is effective against a variety of disorders, including obesity, dyslipidaemia, and cerebral palsy.] Shoshana (absorption) and Kapha Medohara are two features it possesses. Its importance and benefits on different psycho-physical factors have also been demonstrated. In this review article, a detailed assessment of the Udvartana including its importance and benefits.is explained